1911 Wis. Sess. Laws 227-28, ch. 223, § 1. - (:unkn) unknown (My University, 1911)
§ 1. . . § 4393a-1. It shall be unlawful for any person, firm, or corporation to manufacture gunpowder or black blasting powder in any quantity whatsoever within the corporate limits of any city or village or within one hundred rods of any occupied dwelling house or any church, schoolhouse, town hall, depot or other place in which people are accustomed to assemble. § 4393a-2. It shall be unlawful for any person, firm or corporation engaged in the manufacture of gunpowder or black blasting powder to store, or permit to be stored on the land or premises where gunpowder or black blasting powder is manufactured, any dynamite or explosive other than that manufactured at such gunpowder or black blasting powder manufacturing plant or within one mile of any plant where gunpowder of black blasting powder is manufactured.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER